Jejak Integrasi Indonesia Dari Kilometer Nol: Melacak Akar Budaya Nasional Bangsa - Abdul Jalil Salam (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2014)
The founders of the Indonesian people are well aware that the nations of Indonesia was built based on common history, common struggle, as well as the ideals of equality, freedom, security, justice and prosperity in the Republic of Indonesia, which is based on Pancasila and the 1945 Constitution. In this context, the spirit of nationalism respects diversity, pluralism and diversity. In the globalization era, integration of the nation has faced challenges, because the dynamics of the development of the strategic environment have brought a new feel to the levels of interaction, interrelation and interdependence of society, nation and state. Another contributing factor is the shift value between the original nationalism is more oriented to political values and geo-political to the economic value and geo-economics. This value shift from the originally oriented to the importance of unity and unity to form a strong community of nations, be oriented to the accessibility of professionalism to improve the welfare and security for the sake of survival. In this position, the connection to the level of national unity outweighed by the benefit of a more personal nature.